Social partnership: from Lemass to Cowen - Roche, William K. (Economic & Social Studies, 2009)
Dull and predictable though it may be, especially when contrasted with the ?heroic? era of labour and industrial relations during the first two decades of the twentieth century, the theme of social partnership is of undoubted importance. It is of course important for Ireland, given that it has been pivotal to industrial relations, politics and public policy over a period of more than twenty years. While commentators differ on the weighting social partnership should receive in accounting for Ireland?s economic recovery and unprecedented performance over much of the period since, few deny that its role was significant. Some indeed claim that it has fundamentally altered the ?rules of the game? of economic governance in modern Ireland. But Irish social partnership is of more than national significance and interest. A salient feature of the past twenty years has been the interest shown in the Irish case by some of the most distinguished international scholars of the age in the fields of industrial relations, politics and economics. Our subject matter, therefore, is of no small importance, either for our understanding of modern Ireland or for what may be learned from the Irish case with respect to ?social pacts? in general over the past two decades.
The 2008 Countess Markievicz Memorial Lecture of the Irish Association for Industrial Relations. Delivered at Trinity College, Dublin, on 25 November 2008
Keywords: Social partnership; Industrial relations; Ireland; Public policy